Słowo Niepodległe . [miesięcznik studentów i młodzieży katolickiej], no. 24-25, 1989 - [ed. committee] (Ruch Katolickiej Młodzieży Niepodległościowej, 1989)
Motto: "Let us not desire a Poland which does not demand from us any sacrifices". John Paul II